(3GdbGfhf GdeSYhOis - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI hagQS CHhGH GdebGdGJ GdCMOi YTQ (B: (3GdYGde HcdjJg LSe eSJOjQ GdTcd eJfGg ai MhGTjg HYVg SGcf ai Lhag s
(3BNQgG (B:s
(3JeJ GdebGdg GdMGOjI YTQ hJe HJeGegG GdbGfhf GdeSYhOi s
(3ajgG cKjQ ef GdQShe GdgfOSjI hGdLOGhds
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
Keywords: (3Gdadcs